Transformasi Produk Lokal menjadi Usaha Bernilai Tambah: (Studi Pemberdayaan UMKM di Desa Tegalweru) - Ghozy Alfaris Purnawarman; Andri Prasetyo; Rafi Akbar Cantayudha; Feby Ayu Syaharani; Fernanda Puti Maharani Yunanta; Muhammad Hasyim Asy Syamsi; Alya Syifarainy Larasati; Muhammad Faiq Zakaria; Jihan Putri Utami; Whitney Andina Blessia Putri; Najla Padmadaisy Nariswari (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
The Community Service Program (KKN) of Universitas Sebelas Maret, Group 217, conducted in Tegalweru Village, Dau District, Malang Regency, was designed to strengthen local economic capacity through strategies of value-added product development and the consolidation of MSME identity based on village potential. The socio-cultural homogeneity of the community, which largely depends on traditional agriculture, creates a paradox between strong social solidarity and weak economic diversification. This condition poses challenges such as limited innovation, low competitiveness, and the underutilization of local resources, thereby necessitating empowerment interventions capable of transforming traditional economic practices into more adaptive and sustainable business models. This study employed a qualitative descriptive approach through participatory observation, semi-structured interviews, and documentation to explore community responses to training on product value addition, packaging, branding, and basic promotional strategies. The findings reveal increased awareness and enthusiasm among MSME actors and housewives to develop local products through simple processing, representative packaging, and distinctive brand identity. These results underscore that KKN not only serves as an implementation of the Higher Education Tri Dharma but also as a strategic empowerment instrument to reinforce the foundation of community-based economic independence. Practically, the program provides a transformative platform for local enterprises, laying the groundwork for sustainable economic development aligned with both global dynamics and the specific needs of rural communities.